Morning glory seed keeps laxative effect while retains less subchronic toxicity after being fried. (6th April 2020) - Ren, Shu-meng; Zhang, Wei; Xu, Xia-jing; Zhou, Ye; Guo, Jing-yan; Zhang, Xiao-li; Wang, Dong-mei; Pan, Ying-ni; Liu, Xiao-qiu
Abstract: Ethnopharmacological relevance: Morning glory seed (MGS), has been widely used in treating constipation especially towards children. Clinically, people usually take fried MGS (MGSF) in formulas to reduce its side effect. However, the safety of MGSF other than MGS has yet to be explored. Objective: The study aimed to reveal the potential mechanisms of using MGSF instead of MGS basing on chemistry, pharmacodynamics and toxicology. Methods: The chemical compositions of the extracts of MGS and MGSF were compared using UPLC-Q-TOF/MS method. Simultaneously, to prove the availability and safety of MGSF, we investigated the laxative effect and subchronic toxicity of MGS and MGSF and addressed the mechanism of laxative effect of them. Results: In this study, less phenolic acids and more fatty acids were detected in MGSF compared with the compounds in MGS. Moreover, we found that MGS group had stronger laxative effect than MGSF group via downregulating the expression of AQP3 protein. As for subchronic toxicity test, the body weights of MGS group were lower than MGSF group. In serum biochemistry and histopathological examinations, MGS group could cause more serious toxicity in liver, kidney and colon than MGSF group with higher values of BUN, Cr, AST and ALP. Conclusion: Based on the findings in this study, MGSF with varied compounds contents could still keep the laxative effect while retain less subchronic toxicity, which emphasized the necessity of processing and provided an insight into the rational use of MGSF in clinical practice. Graphical abstract: Image 1 Highlights: 16 compounds were identified and compared between MGS and MGSF for the first time using UPLC-Q-TOF/MS. MGS and MGSF groups exerted laxative effects via downregulating the expressions of AQP3 protein. MGSF had less subchronic toxicity in the liver, kidney and colon than MGS while kept laxative effect.